(Sb7Te8)5+ – A Double Cube Shaped Polycationic Cluster 2. Issue 2 (8th January 2013) - Eich, Andreas; Schlüter, Stefan; Schnakenburg, Gregor; Beck, Johannes
Abstract The reactions of antimony and tellurium in molten GaCl3 or AlCl3 in the presence of MCl (M = Li, Na, In, Cu) and SbCl3 as the oxidant yield (Sb7Te8)[Ga2Cl7]2[GaCl4]3 (1), (Sb7Te8)[Ga2Cl7]3[GaCl4]2 (2), Na(Sb7Te8)[GaCl4]6 (3) and Na(Sb7Te8)[AlCl4]6 (4). All compounds form orange, highly air sensitive crystals, which grow inside a viscous melt. The crystal structures are built from [GaCl4]–, [Ga2Cl7]–, and [AlCl4]– anions and discrete (Sb7Te8)5+ cationic clusters. The cations have the structure of two cubes sharing one corner and alternating Sb/Te occupancy of the atom positions. The central position at the joint of the two cubes is occupied by antimony, which exhibits an octahedral coordination. All other antimony and tellurium atoms are in threefold trigonal‐pyramidal coordination. Density functional calculations reveal D3d as the minimum energy molecular symmetry. Analysis of the wave function using the natural bond orbital partitioning scheme comprises three bonding and three non‐bonding orbitals, leading to an overall bond order of 0.5 in terms of classical three‐center, four‐electron bonds for the central antimony atom. Compound 4 undergoes a phase transition at 177 K. The dynamic disorder of the Na+ ion in the room temperature form is resolved into two discrete positions in the low temperature form. The transition is of mainly second order but with some discontinuance close to Tc.